ANALISIS KESESUAIAN (THREE ANGLE FIT) ANTARA PROGRAM, MANAJEMEN DAN ANGGOTA DALAM MENINGKATKAN PARTISIPASI ANGGOTA PADA KOPERASI PENGEMUDI TAKSI (KOPSI) PEKANBARU - wahyuni, Dini wahyuni Dini; Nas, Syakdanur Nas Syakdanur; Trisnawati, Fenny Trisnawati Fenny (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: Conformity (Three Angel Fit) between program management and members explained the quality level of participation of members of a cooperative. The purpose of this study was to determine the suitability (Three Angle Fit) between programs, management and members in improving the participation of members in the Cooperative Taxi driver (Kopsi) Pekanbaru. The data analysis technique used is quantitative descriptive method. The survey results revealed there is conformance (Three angle fit) program, the management and members in improving partiisipasi cooperative members on taxi drivers. With the average percentage of Three angle fit (three conformity) in this study was 94.7% including the appropriate category and yield enough percentage of member participation in cooperative taxi drivers (Kopsi) already is high that the average total amount that is equal to 96 , 1%.Keywords: Three angle fit, programs, management, members